1990
DOI: 10.7326/0003-4819-113-9-664
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Rule for Pulmonary Infiltrates

Abstract: Among adults presenting with acute respiratory illness, a prediction rule based on clinical findings accurately discriminated patients with and without radiographic pneumonia, and was used in two other samples of patients without significant decrement in discriminatory ability. This rule can be used by physicians to develop more effective strategies for detecting pneumonia and for helping to determine the need for radiologic study among patients with acute respiratory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
19

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(119 citation statements)
references
References 20 publications
4
96
0
19
Order By: Relevance
“…However, evaluation of a clinical prediction rule for pulmonary infiltrates in adult patients with acute respiratory illness found that cough, sputum production, and dyspnea were equally common in patients with and without pneumonia. 35 Although not measured in the present study, variation in patient expectations and demands for antibiotics could contribute to the high rates of antibiotic use for acute bronchitis. Some patients seek care for acute respiratory illnesses, such as upper respiratory infections, with the explicit intent of getting a prescription for antibiotics, [36][37][38] and clinicians appear to prescribe antibiotics in response to these expectations.…”
Section: Discussionmentioning
confidence: 94%
“…However, evaluation of a clinical prediction rule for pulmonary infiltrates in adult patients with acute respiratory illness found that cough, sputum production, and dyspnea were equally common in patients with and without pneumonia. 35 Although not measured in the present study, variation in patient expectations and demands for antibiotics could contribute to the high rates of antibiotic use for acute bronchitis. Some patients seek care for acute respiratory illnesses, such as upper respiratory infections, with the explicit intent of getting a prescription for antibiotics, [36][37][38] and clinicians appear to prescribe antibiotics in response to these expectations.…”
Section: Discussionmentioning
confidence: 94%
“…For example, assuming that the pretest probability of pneumonia in outpatients with acute cough is 10% (odds 1:9) 38 , a finding of asymetric expansion of the chest would increase the odds to 8:9, i.e., increase the post-test probability to 47%. Assuming a pretest probability of pneumonia of 12-30% (odds 1:9-3:7) among emergency room patients with fever and acute respiratory symptoms 41 , a finding of pleural friction rub would increase the odds of pneumonia to 5:9-15:7 or to a posttest probability of 36-68%. Future studies should explore whether the various respiratory PE signs provide independent information.…”
Section: Discussionmentioning
confidence: 99%
“…For example, considering pulmonary embolism and pneumonia predicting rules for our patient, the pre-test probabilities are about 16 and 40%, respectively, according to Wells and Heckerling [6,7].…”
Section: A Probabilistic Approach To Diagnosismentioning
confidence: 99%